Female migrants and online market participation in rural Southeast Asia - Trung Thanh Nguyen; Manh Hung Do (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
This research aimed to examine the factors affecting the participation of female ruralurban migrants in online marketplaces, the welfare gains and their distribution from the participation. Our analysis was based on the data of 373 female rural-urban migrants in Thailand and Vietnam. Online market participation is classified into three activities, financial transaction, trading, and business. We accounted for the endogeneity issue of online market participation in welfare impact assessment by using an instrumental variable approach. Our results show that the participation has a positive effect on the consumption of female migrants only when they participate in the complete bundle of online market activities. In addition, we also find that the poor benefit insignificantly from online marketplaces. This raises a concern of increasing welfare inequality and suggests that the poor should be supported in order not to be left behind.
Keywords: O18; R11; I30; 330; Impact; Welfare; Poverty; Endogenous; Heterogeneity; Instrumental variable